Trans* Politics: Current Challenges and Contestations Regarding Bodies, Recognition, and Trans* Organising - Verloo, Mieke (2020)
This thematic issue analyses trans* politics, and the problems and policies articulated by societal, political and legal actors in national and international contexts in Europe and Latin America. Trans* issues are at the heart of politics concerning sex and gender, because the sex binary ordering is producing the categories, identities, and related social relationships around which gender inequalities are constructed. Scholarship on trans* politics promises to bring more fundamental knowledge about how the gender binary organisation of our societies is (dis)functional, and is therefore relevant and beneficial for all gender and politics scholarship. Contestations around trans* issues continue developing, between state and non-state actors, transgender people and medical professionals, and also among and between social movements. This thematic issue is our contribution to dimensions of trans* politics that revolve around the issue of sexed and gendered bodies (the making and unmaking of “deviant” bodies, non-binary language about bodies, and voice given in bodily re/assignments), the limits of recognition (undermining of trans* agency, persistent binary thinking, and disconnect with material dimensions of gender justice), and the potential of trans* movements (processes and practices through which political claims are generated in the movement, a more forward looking and pro-active perspective on the possibility of alliances between the feminist and the trans* projects, and between the trans* project and the disability project, and alliances of movement actors with institutional power holders such as international courts).